Effects of a relational model in the construction of loyalty relationships between candidates in public elections and their voters through the structural equations method (Revista de Investigaciones Universidad del Quindío, 2022)
This research proposes and tests a relational model by analyzing the elements that make it up (satisfaction, trust, attitudinal and behavioral loyalty), which explain its influence on the construction of quality relationships established by candidates running for elected public office. popular with the electorate. The methodology considers the analysis of Structural Equation Models through Partial Least Squares, on a sample of 1037 inhabitants of voting age residing in one of the eight Municipal Police Stations under study belonging to Navojoa, Sonora, Mexico. The main results show that the latent variable satisfaction explains overwhelmingly the trust of the voters (voters); Among other relationships, the trust variable is presented as a significant precedent of loyalty (attitudinal and behavioral), however, the direct relationship between satisfaction and attitudinal and behavioral loyalty was not significant. The study is considered a precursor to testing a relational model during the exercise of an election day, providing valuable findings for future research that extends its study and helps explain the generalized behavior of its variables.
Keywords: Relationship quality; trust; loyalty; SEM PLS